Reyog Kendang Art Studio Dhodhog Sadjiwo Djati in Gendingan Village Kedungwaru District Tulungagung Regency 1984-2009 - huldan Aulia afandi; sugiyanto sugiyanto; sumarno sumarno (JURNAL HISTORICA, 2019)
Reyog kendang is a unique art in Tulungagung. In the village of Gendingan there is an art studio founded by Siswoyo since 1984. The problem that will be examined inthis study is how the background of the establishment and development of reyogkendang art studio Dhodhog Sadjiwo Djati from 1984 to 2009. This study useshistorical research methods consisting of stages of the process consisting of 4 steps,namely: 1. Heuristics; 2. Criticism; 3. interpretation; and 4. Historiography. Theresults of this study are the development of the studios studied mainly in costumesand dance moves. Costumes include the addition of supporting accessories while inthe movement there are added creative movements aside from the standard motion.In 2009 the reyog kendang art got a copyright from IPR. Suggestions in this studyare expected to be a reference in the development of cultural history writing,especially traditional arts and provide information about reyog kendang dhodhogart.